1997
DOI: 10.1097/00003246-199707000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of myasthenic crisis

Abstract: None of the therapeutic regimens applied demonstrated any advantage over the others. All three regimens used were found to be effective and should be applied depending on the circumstances prevailing. Patients with myasthenic crisis must undergo careful cardiac monitoring, and temporary pace-making should be provided where clinically indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
1
11

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 43 publications
0
95
1
11
Order By: Relevance
“…Further studies are needed to examine the associations between the sputum Definition of abbreviations: PPV = positive predict value; NPV = negative predict value; RSBI = rapid shallow breathing index; Pimax = maximal inspiratory pressure; Pemax = maximal expiratory pressure Definition of abbreviations: RSBI = rapid shallow breathing index; Pemax = maximal expiratory pressure quality, suction frequency, and extubation outcome in these patients. Ventilation failure is a common cause of mortality among MG patients [8,24,25], but few previous studies have examined the impact of extubation failure. In a study of general medical patients in a tertiary teaching hospital, Epstein et al reported that extubation failure was associated with a higher mortality, a longer ICU stay, and the requirement to transfer them to a long-term care or rehabilitation facility [18].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to examine the associations between the sputum Definition of abbreviations: PPV = positive predict value; NPV = negative predict value; RSBI = rapid shallow breathing index; Pimax = maximal inspiratory pressure; Pemax = maximal expiratory pressure Definition of abbreviations: RSBI = rapid shallow breathing index; Pemax = maximal expiratory pressure quality, suction frequency, and extubation outcome in these patients. Ventilation failure is a common cause of mortality among MG patients [8,24,25], but few previous studies have examined the impact of extubation failure. In a study of general medical patients in a tertiary teaching hospital, Epstein et al reported that extubation failure was associated with a higher mortality, a longer ICU stay, and the requirement to transfer them to a long-term care or rehabilitation facility [18].…”
Section: Discussionmentioning
confidence: 99%
“…The patient usually spends half of this time intubated in the intensive care unit [8,9,13,20•,Class III]. Approximately 25% of patients are extubated on hospital day 7, 50% by hospital day 13, and 75% by hospital day 31.…”
Section: Thymectomymentioning
confidence: 99%
“…Other than surgical treatment, because perioperative infections and psychological stress could be among the causes of MG crisis, they should be prevented [123][124][125]. Risk factors for the development of postoperative crisis include preoperative worsening of MG symptoms, bulbar symptoms, high blood levels of anti-AChR antibodies, a prior history of crisis, age C50 years, and vital capacity B2.0 L [122,126].…”
Section: Causes and Risk Factorsmentioning
confidence: 99%
“…Common triggers for MG crisis include changes in medications, infections, and surgical stress [123,129]. In the perioperative period, drug changes and infections are particularly important triggers.…”
Section: Elimination Of Triggersmentioning
confidence: 99%